(untitled) (Fractal: Journal of Psychology, 2013)
This work aims to establish a dialogue between the movie “The Phantom of the Opera (2004)” by Joel Schumacher, with the application of Jungian concepts. We seek to understand the film following the interpretative model proposed by Franz, which is used in Fairy Tales. We applied Jungian categories to narrative film, with the main plot an example of the difficulty of the heroine of the film with the male, that is the consequence of aspects not included in its shadow, ie a feminine identification that place as a woman and not just as daughter, girl, puela. The non-integrated aspects relate to her female sexuality, her anima. The complex possess Christine, he favors what aspects of her femininity are not integrated into the ego.